2005
DOI: 10.1063/1.2005394
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature plasma waves resonant detection of sub-terahertz radiation by nanometer field-effect transistor

Abstract: We report on room-temperature, resonant detection of 0.6THz radiation by 250nm gate length GaAs∕AlGaAs heterostructure field-effect transistor. We show that the detection is strongly increased (and becomes resonant) when the drain current increases and the transistor is driven into the current saturation region. We interpret the results as due to resonant plasma wave detection that is enhanced by increasing the electron drift velocity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
112
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 155 publications
(115 citation statements)
references
References 15 publications
2
112
0
1
Order By: Relevance
“…(ii) strong nonlinearity of current flowing along the channel governed by a gate, (iii) possibility of tuning the frequency of 2D plasma waves excited in the channel under the gate by varying the gate potential [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…(ii) strong nonlinearity of current flowing along the channel governed by a gate, (iii) possibility of tuning the frequency of 2D plasma waves excited in the channel under the gate by varying the gate potential [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Both these effects lead to increasing of the effective quality factor wt, which as mentioned before, should be higher than unity to get resonant detection. As discussed in our earlier work [16,17], with increase of the current, the electron drift velocity v increases leads to the increase of an effective relaxation rate given by 1…”
Section: Room Temperaturementioning
confidence: 78%
“…Recently, Teppe and co-workers have demonstrated room-temperature, resonant detection of sub-terahertz radiation by 250 nm gate length GaAs/AlGaAs transistor [17]. They have shown that the detection regime, initially nonresonant, becomes resonant even at 300 K by increasing the drain current and driving the transistor into the current saturation region.…”
Section: Room Temperaturementioning
confidence: 99%
“…For ω 0 τ 1, the linewidth 1/τ is small and FET operates as a resonant detector. Resonant and non-resonant detection of THz radiation by two-dimensional plasma waves was demonstrated several times using a commercial GaAs/AlGaAs FET at cryogenic [5] and room temperature [6][7][8] and using different laboratory THz sources such as backward wave oscillator (BWO), Gunn diodes, molecular lasers, etc. .…”
Section: Introductionmentioning
confidence: 99%